ERK Dephosphorylation through MKP1 Deacetylation by SIRT1 Attenuates RAS-Driven Tumorigenesis - Kwon, Ok-Seon (Cancers (Basel), 2020)
The role of Situin 1 (SIRT1) in tumorigenesis is still controversial due to its wide range of substrates, including both oncoproteins and tumor suppressors. A recent study has demonstrated that SIRT1 interferes in the Kirsten rat sarcoma viral oncogene homolog (KRAS)-driven activation of the Raf-mitogen-activated protein kinase (MAPK)/extracellular signal-regulated kinase (ERK) kinase (MEK)-ERK pathway, thereby inhibiting tumorigenesis. However, the molecular mechanism of SIRT1 as a tumor suppressor in RAS-driven tumorigenesis has been less clearly determined. This study presents evidence that the ectopic expression of SIRT1 attenuates RAS- or MEK-driven ERK activation and reduces cellular proliferation and transformation in vitro. The attenuation of ERK activation by SIRT1 results from prompt dephosphorylation of ERK, while MEK activity remains unchanged. We identified that MKP1, a dual specific phosphatase for MAPK, was deacetylated by SIRT1. Deacetylation of MKP1 by direct interaction with SIRT1 increased the binding affinity to ERK which in turn facilitated inactivation of ERK. Taken together, these results suggest that SIRT1 would act as a tumor suppressor by modulating RAS-driven ERK activity through MKP1 deacetylation.